Testing complex hypotheses using secondary data analysis: is the association between sexual abuse and psychosis moderated by gender in a large prison sample?. Issue 2 (5th May 2015) - Shevlin, Mark; Murphy, Jamie; Read, John
Abstract : Purpose: – There have been many studies that demonstrated an association between sexual trauma and psychotic disorders or psychotic symptoms. Limited attention has been paid to gender differences regarding this association. A recent study evidenced that the trauma-psychosis association may be moderated by gender and that the effect may be specific for females. However, there have been many methodological limitations, particularly that low prevalence of psychosis and sexual trauma for males leads to low statistical power, that have made this hypothesis difficult to test. The paper aims to discuss these issues. Design/methodology/approach: – This study sought to estimate the association between sexual trauma and psychosis, and to determine if the association was moderated by gender using data from the Survey of Psychiatric Morbidity among Prisoners in England and Wales ( n =3, 142). Findings: – Bivariate analysis showed that sexual trauma predicted probable psychosis for both females (OR=4.13) and males (OR=4.72). After controlling for confounding variables the odds ratios for males and females did not differ significantly (the shared odds ratio was 2.60) indicating that the association was not moderated by gender. Originality/value: – The relationship between sexual abuse and psychosis may neither be specific to, nor moderated by, gender.